Budaya Populer: Representasi dalam Film “My Generation” Karya Upi Aviyanto (Jurnal Kajian Media, 2019)
As time goes by, culture society has changes in generation from the past time to the present. So, each generation has their own habits and characteristics in it's time. "My Generation" movie is one of many films that representating social life in the current generation or so-called millenial generation. But this film was negatively received by audience. Because on the movie footage that presented by teaser and trailer watched by people on Youtube, many of them has opinion that is the movie was not in accordance with the Indonesian culture generally. And this movie became a bad influence for the teenagers who watch My Generation. This movie tells the story about four friends. Orly (Alexandra Kosasie), Suki (Lutesha), Konji (Arya Vasco), and Zeke (Bryan Warow). They're dare to express their anxiety to the parents, the teachers, and the school system. It was proven by their video which uploaded to the social media Youtube and then became viral at their school. Untill they're get punished for not going on vacation. The ordinary holiday, eventually bring them to the events and adventure that give a very meaningful lesson for their lives.Keywords: Pop Culture, Mileniall Generation, Life Style